Development of a complementary line for vichy's capital soleil offer (2009)
This thesis project was brought to life with anopportunity given to this group by a company marketing game called Brandstorm L‟Oreal 2008.Attracting over 15,000 students since its launch, reaching out to more than 270 schools, embracing 40 different countries last year, and growing more each year... L‟Oréal Brandstorm is an international marketing game. It is a game which touches upon the core of the art of marketing, allowing students throughout the world to put themselves in the place of a L‟Oréal brand manager and giving them the chance to innovate one of L'Oréal's existing international brands. Students use their marketing knowledge and creativity to develop an international brand strategy, design new packaging and develop a real communication campaign with a world famous advertising agency